Ransom, revenge, and heroic identity in the Iliad - Wilson, Donna F., 1953- (Cambridge University Press, 2002)
Wilson offers a fundamentally new reading of the quarrel between Agamemnon and Achilleus, presenting a detailed anthropology of compensation in Archaic Greece, and demonstrating how the struggle over definitions was a central feature of elite competition for status in the fluid ranking system of Homeric society.